2014
DOI: 10.1039/c4cc00536h
|View full text |Cite
|
Sign up to set email alerts
|

A two-step O- to C-glycosidic bond rearrangement using complementary glycosyltransferase activities

Abstract: An efficient 2'-O- to 3'-C-β-d-glucosidic bond rearrangement on the dihydrochalcone phloretin to convert phlorizin into nothofagin was achieved by combining complementary O-glycosyltransferase (OGT) and C-glycosyltransferase (CGT) activities in a one-pot transformation containing catalytic amounts of uridine 5'-diphosphate (UDP). Two separate enzymes or a single engineered dual-specific O/CGT were applied. Overall (quantitative) conversion occurred in two steps via intermediary UDP-glucose and phloretin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…However, this conversion of 1 into 1 a was not observed with only MiCGT (Figure S3 in the Supporting Information) or Os CGT . These unique results inspired our interest in how this enzymatic conversion of 2‐ O ‐ into 3‐ C ‐glucoside occurred: through chemical Fries‐type O / C ‐glucosidic bond rearrangement or an aglycone intermediate followed by a Friedel–Crafts‐like reaction . To verify these predictions, a mixture of 1 , UDP and MiCGTb was incubated at 30 °C from 10 to 60 min, and the time course of the reaction was monitored by HPLC, which clearly indicated the formation of aglycone phloretin ( 1 b , Figure B).…”
Section: Figurementioning
confidence: 53%
See 1 more Smart Citation
“…However, this conversion of 1 into 1 a was not observed with only MiCGT (Figure S3 in the Supporting Information) or Os CGT . These unique results inspired our interest in how this enzymatic conversion of 2‐ O ‐ into 3‐ C ‐glucoside occurred: through chemical Fries‐type O / C ‐glucosidic bond rearrangement or an aglycone intermediate followed by a Friedel–Crafts‐like reaction . To verify these predictions, a mixture of 1 , UDP and MiCGTb was incubated at 30 °C from 10 to 60 min, and the time course of the reaction was monitored by HPLC, which clearly indicated the formation of aglycone phloretin ( 1 b , Figure B).…”
Section: Figurementioning
confidence: 53%
“…The same result was also obtained when MiCGTb and 1 were incubated with UDP (Figure ). However, this conversion of 1 into 1 a was not observed with only MiCGT (Figure S3 in the Supporting Information) or Os CGT . These unique results inspired our interest in how this enzymatic conversion of 2‐ O ‐ into 3‐ C ‐glucoside occurred: through chemical Fries‐type O / C ‐glucosidic bond rearrangement or an aglycone intermediate followed by a Friedel–Crafts‐like reaction .…”
Section: Figurementioning
confidence: 99%
“…Resveratrol triglucoside was also not formed. As pH could influence resveratrol glucosylation (by affecting reaction kinetics or thermodynamics),26 we carried out reactions over pH 6.0–8.0: optimum conversion was around pH 8.0. The pH‐dependent distribution of glucosylated products (Figure S2) can be explained by the increased reaction rate at high pH.…”
Section: Methodsmentioning
confidence: 94%
“…It demonstrated that MiCGT appeared to generate only C-glycosides with 2,4,6-tri-hydroxy acceptors at the Aring (1-13), both Cand O-glycosides with 2,4-di-hydroxyl acceptors at the Aring (14)(15)(16), and only O-glycosides with 2-or 4-mono-hydroxy acceptors at the Aring (38, 39). Thes ame results were observed with simple phenolics (26-36).…”
mentioning
confidence: 96%